2003
DOI: 10.1124/jpet.102.044073
|View full text |Cite
|
Sign up to set email alerts
|

Structural Requirements for Functional Interaction of Glutathione Tripeptide Analogs with the Human Multidrug Resistance Protein 1 (MRP1)

Abstract: The human multidrug resistance protein 1 (MRP1) is a primary active transporter of reduced (GSH) and oxidized glutathione, as well as GSH-, glucuronate-, and sulfate-conjugated organic anions. In addition, the transport of certain MRP1 substrates is stimulated by the presence of GSH. To evaluate the structural features of GSH required for interaction with the protein, we investigated the ability of a series of GSH analogs to enhance GSH stimulatable transport of [ 3 H]estrone 3-sulfate (E 1 SO 4 ). We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 33 publications
5
40
1
Order By: Relevance
“…This observation was again not surprising, because MRP1 exhibits a 5-and 10-fold higher affinity for E 2 17␤G and LTC 4 than for MRP2, respectively König et al, 1999). Lastly, the N-acetylcysteine conjugates investigated had no observable effect (up to 1 mM) on MRP1-or MRP2-mediated vesicular transport, as would be expected, as previous studies have demonstrated the critical importance of the ␥-glutamyl residue of GSH for interaction with these transporters (Loe et al, 1996b;Leslie et al, 2003).…”
Section: Discussionsupporting
confidence: 58%
“…This observation was again not surprising, because MRP1 exhibits a 5-and 10-fold higher affinity for E 2 17␤G and LTC 4 than for MRP2, respectively König et al, 1999). Lastly, the N-acetylcysteine conjugates investigated had no observable effect (up to 1 mM) on MRP1-or MRP2-mediated vesicular transport, as would be expected, as previous studies have demonstrated the critical importance of the ␥-glutamyl residue of GSH for interaction with these transporters (Loe et al, 1996b;Leslie et al, 2003).…”
Section: Discussionsupporting
confidence: 58%
“…MRP1 is capable of transporting compounds covalently attached to GSH or through a cotransport pathway . Thus, transport of MMA III was measured in the presence of the nonreducing GSH analog ophthalmic acid, known to stimulate the transport of GSH-dependent MRP1 substrates (Loe et al, 1998;Leslie et al, 2001Leslie et al, , 2003Qian et al, 2001;Peklak-Scott et al, 2005). In the case of MMA III , ophthalmic acid did not substitute for GSH; thus, the free sulfur group of GSH was required for transport.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the presence of GSH (3 mM), ATP-dependent transport of MMA III was observed with an activity of 308 pmol mg Ϫ1 min Ϫ1 . In previous studies, it has been shown that ophthalmic acid and other GSH analogs lacking a free thiol group can substitute for GSH and support the transport of several GSH-dependent MRP1 substrates (Loe et al, 1998;Leslie et al, 2001Leslie et al, , 2003Qian et al, 2001;PeklakScott et al, 2005). These findings indicate that the thiol group of GSH is not required for transport of these substrates and rules out the possibility that formation of a GSH conjugate is critical for the transport to occur.…”
Section: Chemicalsmentioning
confidence: 99%
“…However, it is clear that the Y440F mutation almost entirely eliminates binding of azidophenacyl-GSH, as well as LTC 4 . Because both S-methyl GSH and azidophenacyl-GSH can substitute for GSH in transport of E 1 3SO 4 (Qian et al, 2002;Leslie et al, 2003), Tyr 440 may interact with the GSH moiety of LTC 4 , S-methyl GSH, and azidophenacyl-GSH and thus reduce transport of both LTC 4 and E 1 3SO 4 . Consistent with this suggestion, the Y440F mutation resulted in a major decrease in resistance to all three classes of drugs, transport of, or resistance to which, has been shown to be GSH-dependent (Loe et al, 1996b(Loe et al, , 1998Rappa et al, 1997;Renes et al, 1999).…”
Section: Downloaded Frommentioning
confidence: 99%